2021
DOI: 10.1161/circulationaha.120.049952
|View full text |Cite
|
Sign up to set email alerts
|

Malonate Promotes Adult Cardiomyocyte Proliferation and Heart Regeneration

Abstract: Background: Neonatal mouse cardiomyocytes undergo a metabolic switch from glycolysis to oxidative phosphorylation, which results in a significant increase in reactive oxygen species (ROS) production that induces DNA damage. These cellular changes contribute to cardiomyocyte cell cycle exit and loss of the capacity for cardiac regeneration. The mechanisms that regulate this metabolic switch and the increase in ROS production have been relatively unexplored. Current evidence suggests that elevated RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 36 publications
4
89
1
Order By: Relevance
“…The latter pathway provides acetyl-CoA for the functioning of the TCA cycle and for the acetylation of mitochondrial proteins, particularly of complex I, this process restraining ATP and ROS production [ 109 ]. Of note, citrate, OAA and malonate are well known inhibitors of succinate dehydrogenase (SDH) (or complex II), particularly in liver, brain, cardiac and muscle cells [ 110 , 111 , 112 ]. However, the modulation of SDH by these molecules in cancer cells remains to be studied.…”
Section: The Central Place Of Citrate In Cancer Cells Relying On Oxidative Metabolismmentioning
confidence: 99%
“…The latter pathway provides acetyl-CoA for the functioning of the TCA cycle and for the acetylation of mitochondrial proteins, particularly of complex I, this process restraining ATP and ROS production [ 109 ]. Of note, citrate, OAA and malonate are well known inhibitors of succinate dehydrogenase (SDH) (or complex II), particularly in liver, brain, cardiac and muscle cells [ 110 , 111 , 112 ]. However, the modulation of SDH by these molecules in cancer cells remains to be studied.…”
Section: The Central Place Of Citrate In Cancer Cells Relying On Oxidative Metabolismmentioning
confidence: 99%
“…Notably, in an ischemia-reperfusion model, SIRT5KOs exhibited a larger infarct size, and inhibition of SDH reduced this infarct size in both WT and SIRT5KO mice (16). Furthermore, succinate injection is sufficient to induce cardiomyocyte hypertrophy, while inhibition of SDH results in improved recovery following ischemia-reperfusion (37,38). Our results and those of others have revealed that SIRT5 modulates SDH activity, in a cell-and context-dependent fashion, implying that SIRT5OE hearts may have altered SDH activity, which could contribute to their cardioprotection (8,36,39).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the cardioprotective role of malonate during I/R injury in mouse and pig hearts (105, 107); malonate did not protect against infarction post-MI but rather promoted regeneration following infarction (110). Furthermore, SDH inhibition by malonate following adult MI was accompanied by increased succinate levels as a consequence of TCA cycle inhibition, which is distinct from the cardioprotective role of malonate that prevents succinate accumulation during I/R injury (105,110). Interestingly, metabolic profiling of the adult heart demonstrated an increase in glucose metabolism and a decrease in TCA cycle metabolism following SDH inhibition by malonate, consistent with a metabolic reprogramming from oxidative phosphorylation to glycolysis in the adult heart.…”
Section: Tca Cycle Metabolites In the Heartmentioning
confidence: 91%
“…Interestingly, a recent study demonstrated that metabolic reprogramming to glycolysis promotes cardiomyocyte proliferation and heart regeneration following injury in zebrafish (15). Remarkably, SDH inhibition by malonate promotes adult cardiomyocyte proliferation, revascularization, and heart regeneration following adult myocardial infarction (110). In contrast to the cardioprotective role of malonate during I/R injury in mouse and pig hearts (105, 107); malonate did not protect against infarction post-MI but rather promoted regeneration following infarction (110).…”
Section: Tca Cycle Metabolites In the Heartmentioning
confidence: 99%
See 1 more Smart Citation